2014
DOI: 10.1371/journal.pntd.0002728
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Extensive Wolbachia Symbiont Insertions Discovered in the Genome of Its Host Glossina morsitans morsitans

Abstract: Tsetse flies (Glossina spp.) are the cyclical vectors of Trypanosoma spp., which are unicellular parasites responsible for multiple diseases, including nagana in livestock and sleeping sickness in humans in Africa. Glossina species, including Glossina morsitans morsitans (Gmm), for which the Whole Genome Sequence (WGS) is now available, have established symbiotic associations with three endosymbionts: Wigglesworthia glossinidia, Sodalis glossinidius and Wolbachia pipientis (Wolbachia). The presence of Wolbachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 115 publications
5
57
0
4
Order By: Relevance
“…These regions spanned 100-2,500 bp, which were smaller and more dispersed than those reported in Glossina morsitans (two segments of ∼500 Kb) (9). A previous transcriptome analysis showed that eight of these genes appear to be transcribed in the midgut (10).…”
mentioning
confidence: 82%
“…These regions spanned 100-2,500 bp, which were smaller and more dispersed than those reported in Glossina morsitans (two segments of ∼500 Kb) (9). A previous transcriptome analysis showed that eight of these genes appear to be transcribed in the midgut (10).…”
mentioning
confidence: 82%
“…It is also worth noting that within the bedbug (Cimex lectularius), Wolbachia symbionts are localized to bacteriomes and are associated with nutritional mutualism (82), in stark contrast to the reproductive parasitism resulting from these infections in most other insects. Further, significant portions of the Wolbachia genome have been inserted into the G. morsitans chromosomal DNA (58,83). Future analyses should examine whether these horizontal transfer events are associated with metabolic activity and the extent of these transfers in other tsetse fly species.…”
Section: Discussionmentioning
confidence: 99%
“…LGT of fragments of the Wolbachia genome (total size approximately 1.2 Mb), ranging from 500 base pairs to more than 1 Mb, have been observed in many invertebrates, including beetles (Nikoh et al, 2008), grasshoppers (Funkhouser-Jones, 2015;Toribio-Fernández et al, 2017), wasps (Dunning-Hotopp et al, 2007), fruit flies (Dunning-Hotopp et al, 2007;Klasson et al, 2014;Choi, Bubnell and Aquadro, 2015;Morrow et al, 2015), tsetse flies (Brelsfoard et al, 2014;Nakao et al, 2016), butterflies and moths , kissing bugs (Mesquita et al, 2015), mosquitoes (Klasson et al, 2009;Hou et al, 2014), filarial nematodes (Fenn et al, 2006;Dunning-Hotopp et al, 2007;Keroack et al, 2016) and spiders (Baldo et al, 2008).…”
Section: Uses Of Wolbachia In Control Methodsmentioning
confidence: 99%